Political circumstances and their impact on the transformations of Plato’s political and social thought - Ahmed Majeed Radi (Zien Journals, 2023)
Political circumstances play a major role in crystallizing ideas, formulating them and determining their features among thinkers and philosophers, so their ideas are the result of what they experienced and experienced from political transformations that cast a shadow on the formations of thought. These ideas in the end are nothing but a reflection of the political circumstances experienced by the philosopher Plato, and since political and social thought with a general revelation is a manifestation of human thought, and since the philosopher is a human being, Whatever the degree of his objectivity and his keenness on it, he cannot protect his thought from the influence of the circumstances of his society and the political circumstances of his era. Therefore, the political circumstances of his era, which were represented by the Peloponnesian Wars and the execution of his teacher Socrates, had a great impact on the construction and formation of his political and social thought, which was represented by their permanent connection. The developments witnessed by societies and the circumstances they are experiencing serve as a driving factor towards the production and innovation of ideas. As the intellectual influences that surrounded Plato’s thought, this influence cannot be denied because it represents the first thought of any human being. The first environment plays a major role in moulding the human being into a specific mold. However, this was not enough. Here we do not believe in the unity of the cause, but rather in the multiplicity of causes, as his aristocratic upbringing was due to. There is no denying a major role in the formulation of his thought, but the political circumstances that he experienced had the greatest driving factor on the course of his intellectual transformations, and this is what we are looking for in the course of our research
Keywords: circumstances; denying; intellectual; aristocratic